Diaspora tourism and the negotiation of belonging: journeys of young second-generation Eritreans to Eritrea. Issue 15 (8th December 2017) - Graf, Samuel
ABSTRACT: In this article, I address the diaspora tourism of children of migrants. Based on a case study of second-generation Eritreans, I reveal how journeys to parents' home countries affect the sense of belonging of the second generation. Applying a translocal perspective, I understand diaspora tourism as a translocal phenomenon which is both based on and creates interconnectedness between individuals and places. I illustrate different locally grounded situations and the socio-spatial interconnectedness that second-generation Eritreans experience at various places in the course of their journey in Eritrea. I conclude that diaspora tourism and the associated experiences at the places visited represent crucial identity-establishing events for second-generation Eritreans and influence the negotiation of their belonging and positioning towards both Eritrea and the Eritrean diaspora. This paper contributes to the debate on second generation and belonging by focusing on how localities and socio-spatial interconnectedness affect the negotiation of second-generation Eritreans' belonging.